Colesevelam attenuates cholestatic liver and bile duct injury in Mdr2−/− mice by modulating composition, signalling and excretion of faecal bile acids. Issue 9 (10th April 2018) - Fuchs, Claudia Daniela; Paumgartner, Gustav; Mlitz, Veronika; Kunczer, Victoria; Halilbasic, Emina; Leditznig, Nadja; Wahlström, Annika; Ståhlman, Marcus; Thüringer, Andrea; Kashofer, Karl; Stojakovic, Tatjana; Marschall, Hanns-Ulrich; et al.
Abstract : Background and aims: Interruption of the enterohepatic circulation of bile acids (BAs) may protect against BA-mediated cholestatic liver and bile duct injury. BA sequestrants are established to treat cholestatic pruritus, but their impact on the underlying cholestasis is still unclear. We aimed to explore the therapeutic effects and mechanisms of the BA sequestrant colesevelam in a mouse model of sclerosing cholangitis. Methods: Mdr2 −/− mice received colesevelam for 8 weeks. Gene expression profiles of BA homeostasis, inflammation and fibrosis were explored in liver, intestine and colon. Hepatic and faecal BA profiles and gut microbiome were analysed. Glucagon-like peptide 1 (GLP-1) levels in portal blood were measured by ELISA. Furthermore, Mdr2 −/− mice as well as wild-type 3, 5-diethoxy-carbonyl-1, 4-dihydrocollidine-fed mice were treated with GLP-1-receptor agonist exendin-4 for 2 weeks prior to analysis. Results: Colesevelam reduced serum liver enzymes, BAs and expression of proinflammatory and profibrogenic markers. Faecal BA profiling revealed increased levels of secondary BAs after resin treatment, while hepatic and biliary BA composition showed a shift towards more hydrophilic BAs. Colonic GLP-1 secretion, portal venous GLP-1 levels and intestinal messenger RNA expression of gut hormone Proglucagon were increased, while ileal Fgf15 expression was abolished by colesevelam. Exendin-4 treatment increased bile duct mass without promoting a reactive cholangiocyte phenotype in mouse models of sclerosing cholangitis. Microbiota analysis showed an increase of the phylum δ-Proteobacteria after colesevelam treatment and a shift within the phyla Firmicutes from Clostridiales to Lactobacillus . Conclusion: Colesevelam increases faecal BA excretion and enhances BA conversion towards secondary BAs, thereby stimulating secretion of GLP-1 from enteroendocrine L-cells and attenuates liver and bile duct injury in Mdr2 −/− mice.